2016
DOI: 10.1259/bjr.20160060
|View full text |Cite
|
Sign up to set email alerts
|

Technique and outcome of post-mastectomy adjuvant chest wall radiotherapy—the role of tissue-equivalent bolus in reducing risk of local recurrence

Abstract: Objective: Adjuvant chest wall radiotherapy is used in patients with high-risk histological features post-mastectomy to reduce the risk of locoregional recurrence. Treatment can be given with or without a tissue-equivalent bolus to increase skin surface dose. The additional benefit of using a bolus remains unclear; however, it is known to be associated with a higher incidence of skin toxicity. This study compared chest wall recurrence and skin toxicity in patients treated with and without a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Based on the lack of evidence-based causation between changes in dose and potential recurrence, there is variability of bolus application in a clinical setting. Some physicians may not find that the benefits of the bolus outweigh the associated risks, namely the increased risk of RD [6,14,17,18]. Skin toxicity is an exceedingly common side effect of RT which can be very painful, may lead to long-term sequelae such as undesirable cosmesis, fibrosis, chronic pain, hyperpigmentation, and telangiectasia, and can decrease quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the lack of evidence-based causation between changes in dose and potential recurrence, there is variability of bolus application in a clinical setting. Some physicians may not find that the benefits of the bolus outweigh the associated risks, namely the increased risk of RD [6,14,17,18]. Skin toxicity is an exceedingly common side effect of RT which can be very painful, may lead to long-term sequelae such as undesirable cosmesis, fibrosis, chronic pain, hyperpigmentation, and telangiectasia, and can decrease quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to find a balance between tolerable skin toxicity and adequate treatment to the skin. Turner et al followed up 314 postmastectomy patients and found that among the 101 patients treated with bolus, 75% had grade 1-2 acute skin toxicity compared with 57.3% of those treated without bolus (P ¼ .002) [14]. Abel et al [6] reported that 70% of patients treated with bolus compared with 42% of those treated without a bolus developed !…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 Furthermore, this study cannot speak to the implications for use of skin bolus in the postmastectomy setting, which varies at our institution, but is commonly applied, usually in an every-other-day fashion or daily until a Grade 2 reaction develops. 18 …”
Section: Discussionmentioning
confidence: 99%
“…The ability to spare the skin is very useful for many different types of cancer, however, there is a problem with the treatment of superficial lesions near the skin surface. Thus, a build-up material (bolus) is placed in direct contact with the patient’s skin surface in order to increase the superficial dose and improve dose uniformity by compensating for missing tissue [46]. Normal organs including lung and heart could be protected because bolus brings isodose lines toward the surface and it was demonstrated that the use of bolus in the postmastectomy radiotherapy reduced the normal tissue complication probabilities (NTCPs) of the ipsilateral lung [7].…”
Section: Introductionmentioning
confidence: 99%